Celebrating the innovation and quality month in UiTM 2025 - Ariffin, Nur Syamimi; Aziz, Hamzah (Faculty of Pharmacy, 2025)
University Teknologi MARA (UiTM) organises Innovation and Quality Month annually, hosted by a selected faculty across its various campuses nationwide. As the host of this year’s event, the Faculty of Pharmacy collaborated with the Institute of Quality and Knowledge Advancement (InQKA) and UiTM Global (UG) in organising the programme. Everyone contributed their best efforts, from brainstorming the theme for this year’s event to getting all of us on the same page and reaching consensus, despite the hiccups we faced prior to the launching day.